The Diagnostic Efficacy of Some Tumor Biomarkers for Breast Cancer Concerning Histopathological Examinations - Radhi, Adel Nazum; Mahdi Murshid Thwaini; Hamed Jaddoa Abbas (Journal of Biomedicine and Biochemistry, 2024)
Background Breast cancer (BC) remains the primary cause of mortal- ity related to cancer. There is an increasing need for developing new and efficient diagnostic methods for early detection and diagnosis. Purpose This study compared histopathological biopsies to tumor biomarkers (Serum P53, cathepsin D, cyclin E, and nestin) in diagnosing breast cancer. Methods A case-control research included 60 breast cancer patients and 30 healthy controls. ELISA measured serum P53, cathepsin D, cyclin E, and nestin. The study found substantial increases (P < 0.01) in Nestin and Cyclin E levels in BC patients compared to the control group. Results The study found a substantial drop (P < 0.01) in P53 levels in BC patients compared to the control group.The study found a substantial rise (P value < 0.01) in Nestin and cyclin E levels in BC patients with stage IV compared to early stages, but P53 decreased in increasing stages.There was a substantial positive connection (P < 0.05) between Cathepsin-D and cyclin E levels (r= 0.210). A strong negative connection (P < 0.01) exists between nestin levels and P53 levels (r= -0.406). The AUC analysis revealed sensitivity values of 0.33% and 0.43 for Nestin, P 53, Cathepsin- D, and Cyclin E markers, respectively. The study found sensitivity values of 0.62, 0.36, 0.40, 0.65, 0.20, and 0.33 for Nestin, P 53, Cathepsin-D, and Cyclin E markers.Breast cancer patients had higher Nestin and Cyclin E biomarkers and lower P53. Nestin and P53 have good breast cancer detection sensitivity and specificity. Conclusion The study determined that nestin and P53 had a compar- atively high level of sensitivity and specificity in the detection of breast cancer.